1999
DOI: 10.1034/j.1399-0012.1999.130502.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hyperglycemia and hyperuricemia on long‐term transplant survival in kidney transplant recipients

Abstract: Long-term prognosis in kidney transplant recipients depends on multiple factors. The purpose of this study was to quantify the influence of hyperuricemia and hyperglycemia (elements of the so-called 'syndrome X', i.e., a combination of metabolic disorders like hyperuricemia, diabetes mellitus, hyperlipidemia, and hypertension) on organ function in 350 kidney transplant recipients who had received 375 kidney transplants up to 1990 and in whom sex, age of recipient and donor, nephrologic disease, duration of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 21 publications
4
41
2
Order By: Relevance
“…Akgül and associates 4 reported that high UA levels do not have a role on developing chronic allograft nephropathy during the first 3 years after transplant. Gerhardt and associates 12 reported significantly reduced transplant survival rates among hyperuricemic patients compared with those who were normouricemic kidney transplant recipients. In 1 study, male sex, higher body mass index, longer term pretransplant dialysis, and hypertension were associated with the development of hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…Akgül and associates 4 reported that high UA levels do not have a role on developing chronic allograft nephropathy during the first 3 years after transplant. Gerhardt and associates 12 reported significantly reduced transplant survival rates among hyperuricemic patients compared with those who were normouricemic kidney transplant recipients. In 1 study, male sex, higher body mass index, longer term pretransplant dialysis, and hypertension were associated with the development of hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that HUA is only a marker of graft dysfunction, [136][137][138][139] whereas some other studies suggest that UA is an independent risk factor for graft dysfunction. [140][141][142][143][144][145][146] Recently, Hart et al 147 reported that HUA correlated with tubular atrophy and interstitial fibrosis in chronic allograft nephropathy. Similar to the experimental findings, HUA in humans may exacerbate CsA nephrotoxicity.…”
Section: Hua and Renal Transplantationmentioning
confidence: 99%
“…However our study shows a clear relationship between hyperuricemia and derangements in the lipid profile. Progression of the cardiovascular disease with high uric acid levels has also been postulated by many researchers 43,44 .…”
Section: Discussionmentioning
confidence: 85%
“…There are also several studies that shows that increase uric acid is a major risk factor for cardiovascular disease, kidney disease, pregnancy related complications and concomitant mortality 47,48 . Gerhardt et al found out that hyperuricemic patients have lower 5 year survival rate than normouricemic patients 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation